Analysis of the visual quality of the landscape of the Sierra de Guadarrama National Park using indirect procedures: EMC and GIS - asVallina Rodríguez, Alejandro (Anales de Geografía de la Universidad Complutense, 2020)
Faced with the complexity involved in the objective assessment of the landscape, the present investigation proposes a methodological approach from the indirect evaluation of one of the three large blocks (intrinsic, positive and negative incidence) that form the visual quality of any space, fundamentally attending to intrinsic values. The main objective of the analysis will be to decompose all those values and criteria that are part of the inherent visual elements of the landscape of the Sierra de Guadarrama to, based on the use of multicriteria evaluation methodologies (MCE) and their combination with the possibilities offered by Geographic Information Systems (GIS), to get enough knowledge of the visual reality of the environment This will allow to interpret technically the diverse factors that configure the intrinsic values of the Guadarrama, integrating the results in a thematic cartography of the field, which shows in detail the values of visual quality in a territorialized way.